(3GdGbJUGO GdOhdj (B:s (3GdfXQjI h GdSjGSGJ (B/s - (3YHO GdbGOQ, GdSjO eJhdjs ((3YeGf(B: s (3OGQ GdacQ(B, s, 2011)
(3fXQjGJ GdJLGQI GdNGQLjI h SjGSGJgG , ejRGf GdeOahYGJ (B: (3GdfXQjI h GdSjGSI , fXQjI h SjGSI SYQ GdUQa , GdfXGe GdJLGQj h GdfbOj h GdeGdj GdOhdj , hSGFd GdOaY h GdJehjd aj GdJLGQI GdNGQLjIs
Keywords: (3GdGbJUGOs; (3GdGbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs